Akibat Hukum Perkawinan Dibawah Tangan - Rumfaran, Ani; Angga, La Ode; Labetubun, Muchtar Anshary Hamid (PATTIMURA Law Study Review, 2024)
Marriage under hand is a legal marriage if it is carried out according to religion and each belief, but according to the law it is invalid because the marriage is not officially registered at the Office of Religious Affairs or the Civil Registration Office so that it can cause various significant legal consequences, including the loss of legal protection, child status, rights and obligations of husband and wife in administrative difficulties are legal institutions that have a significant impact on individuals and society. This research aims to examine the legal consequences of marriage in the context of positive law in Indonesia. The research method used is normative juridical, using a statutory approach, conceptual approach and case approach. The law used is literature study, journals and internet media. The results of the study indicate that the Legal Status of Marriage Under the Hand in Review of Positive Law in Indonesia is a marriage under the hand or marriage sirri is a marriage that is not registered according to the applicable laws and regulations, so that legally the marriage is considered to have never existed, because it does not have outentik deed evidence. Another legal consequence is that the wife, children and other relatives of the wife cannot claim their legal rights to the husband and even children from the marriage cannot use their birth certificates using their father's name as the name of their parents ever existed, because they do not have proof of authentic deeds.